Enhancing creativity and problem solving skills through creative problem solving in teaching mathematics - Khalid, Madihah; Saad, Supiah; Abd. Hamid, Siti Rafiah; Abdullah, Mohammad Ridhuan; Ibrahim, Hasniza; Shahrill, Masitah (VGTU Press, 2020)
In recent years, calls to nurture and teach creativity from an early age in schools has intensified. Creativity is something regular in the teaching of arts subjects but is not a common feature in teaching science, technology, engineering and mathematics subjects. However, what really matters, is how the subject is being taught. This research aimed to foster creativity through the teaching of mathematics via problem solving that challenges the solving of problems in a creative manner, which is defined as creative problem solving. This quasi-experimental study investigates changes in students learning of mathematics via creative problem solving. Altogether, 172 Form 1 students forming treatment and comparison groups from four schools in Gombak District area, Malaysia were involved. A mixed qualitative and quantitative data were collected to investigate the effect of the 3 cycles of creative problem solving lessons implemented. Instruments used were Torrance Test of Creative Thinking, a mathematics problem solving test and creativity checklist. This paper will only present the quantitative data obtained. Results show statistically significant increases in scores for most categories of creativity and problem solving tests. This research brought together teachers and researchers in trialing creative problem solving to teach mathematics, to achieve the enhancement of students’ creative thinking and problem solving skills. This coincided with the introduction of Kurikulum Standard Sekolah Menengah with new emphasis to strengthen the quality of science, technology, engineering and mathematics education in general, where higher-order thinking reforms are emphasized. *********************************************************************************